A DEEP LEARNING MODEL WITH A NEW LOSS FUNCTION FOR AGE ESTIMATION - MOHAMMED, ARMAN I.; ALI, SARBAST H.; HASSAN, OMER MOHAMMED SALIH; SALIH, SARDAR OMAR (Journal of Duhok University, 2023)
Age estimation is a global challenge in the area of computer vision, as it depends on the facial features of the person. Recently, it has become an important approach for facial recognition problems and many other real-world applications. Accurate age estimation has the potential to improve decision-making processes in various industries and applications. It has been shown that the approach of Convolutional Neural Network (CNN) performs well for age estimation and promising results have been obtained by many researchers. However, the efficiency of CNN, to a great extent, is determined by the strength of the loss function. In this paper, a groundbreaking contribution is introduced, presenting a loss function that effectively calculates the disparity between the real and predicted age labels. Which is driven from Golden ratio and Mean Squared Error (MSE) functions. The proposed loss function is denoted by Golden Mean Squared Error (GMSE). A predesigned CNN is trained with UTKFace and FG-Net age datasets. According to the results, GMSE proved to operate better than preexisted loss functions. The MSE loss at epoch 25 was 51.34 and the GMSE loss at the same epoch was 3.15. At final round of training, the MSE loss was 6.56 and the GMSE loss was 1.58. The Mean Absolute Error (MAE) loss function was also used, but it couldn’t lower the loss below 2 in the last epoch. Furthermore, the GMSE accuracy outperformed both MSE and MAE in the testing phase for both the UTKFace and FG-NET datasets. The GMSE loss function achieved better results than the MSE and MAE loss functions, indicating that it can save time and computations during the training process and provide better results at production phaseAge estimation is a global challenge in the area of computer vision, as it depends on the facial features of the person. Recently, it has become an important approach for facial recognition problems and many other real-world applications. Accurate age estimation has the potential to improve decision-making processes in various industries and applications. It has been shown that the approach of Convolutional Neural Network (CNN) performs well for age estimation and promising results have been obtained by many researchers. However, the efficiency of CNN, to a great extent, is determined by the strength of the lAge estimation is a global challenge in the area of computer vision, as it depends on the facial features of the person. Recently, it has become an important approach for facial recognition problems and many other real-world applications. Accurate age estimation has the potential to improve decision-making processes in various industries and applications. It has been shown that the approach of Convolutional Neural Network (CNN) performs well for age estimation and promising results have been obtained by many researchers. However, the efficiency of CNN, to a great extent, is determined by the strength of the loss function. In this paper, a groundbreaking contribution is introduced, presenting a loss function that effectively calculates the disparity between the real and predicted age labels. Which is driven from Golden ratio and Mean Squared Error (MSE) functions. The proposed loss function is denoted by Golden Mean Squared Error (GMSE). A predesigned CNN is trained with UTKFace and FG-Net age datasets. According to the results, GMSE proved to operate better than preexisted loss functions. The MSE loss at epoch 25 was 51.34 and the GMSE loss at the same epoch was 3.15. At final round of training, the MSE loss was 6.56 and the GMSE loss was 1.58. The Mean Absolute Error (MAE) loss function was also used, but it couldn’t lower the loss below 2 in the last epoch. Furthermore, the GMSE accuracy outperformed both MSE and MAE in the testing phase for both the UTKFace and FG-NET datasets. The GMSE loss function achieved better results than the MSE and MAE loss functions, indicating that it can save time and computations during the training process and provide better results at production phaseoss function. In this paper, a groundbreaking contribution is introduced, presenting a loss function that effectively calculates the disparity between the real and predicted age labels. Which is driven from Golden ratio and Mean Squared Error (MSE) functions. The proposed loss function is denoted by Golden Mean Squared Error (GMSE). A predesigned CNN is trained with UTKFace and FG-Net age datasets. According to the results, GMSE proved to operate better than preexisted loss functions. The MSE loss at epoch 25 was 51.34 and the GMSE loss at the same epoch was 3.15. At final round of training, the MSE loss was 6.56 and the GMSE loss was 1.58. The Mean Absolute Error (MAE) loss function was also used, but it couldn’t lower the loss below 2 in the last epoch. Furthermore, the GMSE accuracy outperformed both MSE and MAE in the testing phase for both the UTKFace and FG-NET datasets. The GMSE loss function achieved better results than the MSE and MAE loss functions, indicating that it can save time and computations during the training process and provide better results at production phase